-3=-6t-3

Simple and best practice solution for -3=-6t-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=-6t-3 equation:


Simplifying
-3 = -6t + -3

Reorder the terms:
-3 = -3 + -6t

Add '3' to each side of the equation.
-3 + 3 = -3 + 3 + -6t

Combine like terms: -3 + 3 = 0
0 = -3 + 3 + -6t

Combine like terms: -3 + 3 = 0
0 = 0 + -6t
0 = -6t

Solving
0 = -6t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '6t' to each side of the equation.
0 + 6t = -6t + 6t
Remove the zero:
6t = -6t + 6t

Combine like terms: -6t + 6t = 0
6t = 0

Divide each side by '6'.
t = 0

Simplifying
t = 0

See similar equations:

| Y=20-6x | | -12.5+0.5p=0.9p+5.3 | | Y=x^2-17x+50 | | 139=3d+2(4d+9) | | 3r=-21 | | 32-2x=20 | | 0=-16t^2+38.8t+3 | | 8x^2-370=0 | | -10=10w-20 | | 8(x+3)=5(k-3) | | 42=6-9h | | 6x^2+2x-9=0 | | 8n-6=9n | | 0.2-0.01(x+2)=-0.03(2-x) | | 2(x-5)=4x-2(x-5) | | -7x+8=-20 | | 4(x-2)+6=6x-2(2+x) | | -1.66x+.66=-11 | | 18m+30=66 | | 2(2+4)= | | 0.4(x+20)-0.8X=44 | | 5(92-5x)=27 | | 0.25n+0.1=9.8 | | 7-4w=-10 | | 6x-15x+-5=58 | | 4d=27 | | X^2+2=3 | | -3(3s-5)-15=-3(7s+1)-5 | | 8y+3(y-7)=3(y+2)-4 | | -x^2-10x=25 | | 0.5x-4.8=-2.3 | | 2/3(x-8)=x+2 |

Equations solver categories